The effect of Ganges river basin irrigation on pre‐monsoon rainfall - Fletcher, J. K.; Birch, C. E.; Keane, R. J.; Taylor, C. M.; Folwell, S. S. (Quarterly journal of the Royal Meteorological Society, 2022)
The first experiment studying the effect of irrigation on pre‐monsoon rainfall in India using a high‐resolution convection‐permitting model has been carried out. This study includes both short (3‐day) experiments and month‐long free‐running simulations, enabling investigation of the effect of irrigation on mesoscale circulations and associated rainfall. In the pre‐monsoon, it is found that irrigation increases rainfall in our simulations. Intriguingly, the rainfall increase found in the high‐resolution model mostly occurs on the mountains near the irrigation rather than over the irrigated region itself. This is because our applied irrigation is in low‐lying regions, and so it enhances the mountain‐valley flows leading to enhancement of diurnally driven orographic rainfall. Because Ganges basin irrigation occurs near mountains which already have some of the highest rainfall rates in the world, and which are subject to flash flooding and landslides, this has significant implications for hazards in mountainous regions during the pre‐monsoon and early monsoon period. High‐resolution simulations of the pre‐monsoon period of South Asia, in which deep convection is explicitly modelled rather than parametrized, show that irrigation in the Ganges river basin region increases rainfall, primarily on mountain slopes and foothills. This occurs by enhancing the mountain‐valley buoyancy gradient which governs the diurnal cycle of orographic flows and related precipitation in the pre‐monsoon period.